A systematic review of patient-reported outcome measures in paediatric otolaryngology. Issue 1 (11th December 2017) - Powell, J; Powell, S; Robson, A
Abstract: Background: Recently, there has been increased emphasis on the development and application of patient-reported outcome measures. This drive to assess the impact of illness or interventions, from the patient's perspective, has resulted in a greater number of available questionnaires. The importance of selecting an appropriate patient-reported outcome measure is specifically emphasised in the paediatric population. The literature on patient-reported outcome measures used in paediatric otolaryngology was reviewed. Methods: A comprehensive literature search was conducted using the databases Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, and PsycInfo, using the terms: 'health assessment questionnaire', 'structured questionnaire', 'questionnaire', 'patient reported outcome measures', 'PROM', 'quality of life' or 'survey', and 'children' or 'otolaryngology'. The search was limited to English-language articles published between 1996 and 2016. Results: The search yielded 656 articles, of which 63 were considered relevant. This included general paediatric patient-reported outcome measures applied to otolaryngology, and paediatric otolaryngology disease-specific patient-reported outcome measures. Conclusion: A large collection of patient-reported outcome measures are described in the paediatric otolaryngology literature. Greater standardisation of the patient-reported outcome measures used in paediatric otolaryngology would assist in pooling of data and increase the validation of tools used.